Status epilepticus induzido por Marinobufogenina, uma substância isolada das glândulas parotóides de Bufo paracnemis Lutz 1925 - Nogueira, Rita Maria Dantas (2000)
The main focus of this research was the isolation of a substance with a strong convulsant action from the secretions of the toad Bufo paracnemis, Lutz, parotid glands, determination of its chemical structure and its behavioral and electrographic effects on central nervous system. This substance was purified in large amounts using a reverse-phase high-performance liquid chromatography (HPLC), with a C-18 preparative column (shim-pack prep. ODS 2,5 x 30 cm). Its chemical structure was elucidated using high resolution Nuclear Magnetic Resonance analysis, allowing its identification as a steroid of the bufodienolide type, already known in the literature as Marinobufagin (14beta-15beta-epoxy-3beta,5beta-dihidroxy-20,22-bufadienolide). Our results based on behavioral and electrographic analysis showed central effects induced by systemic administration of Marinobufagin in rats and mice. The animals presented severe neurotoxic effects as circle-like movements, tachypnea, mild tremor of the head , a whole body tremor , myoclonic movements of the fore or hindlimbs, tonic-clonic seizures and death. Marinobufagin DL50 was 10.5 ± l.5 mg/kg for mice and 25.0 ± 2.0 mg/kg for rats, both through intraperitoneal injection. This strong convulsant activity is dose-dependent and 5.0 mg/kg doses for mice and 20.0 mg/kg for rats, both intraperitoneal (IP), already showed behavioral changes that evolved to generalized tonic-clonic seizures. Marinobufagin induced seizures that ended up in status epilepticus that lasted more than an hour. Seizures decreased in almost 80% of the animals treated with Diazepan (10.0 and 12.5 mg/kg, IP) even though some of these animals continued to show seizures in the electrographic recordings. Phenobarbital didn’t block seizures induced by Marinobufagin. Phenitoin was able to block generalized tonic-clonic seizures in all animals of the group, suggesting an action involving changes in monovalent cations. Our results suggest that Marinobufagin could represent a pharmacological tool for the development of an epilepsy experimental model, since it had fulfilled the following requirements: i) showed epileptiform activity in electrographic recordings; ii) seizures were blocked by anticonvulsant drugs such as Diazepan and Phenitoin, an essential requirement for the evaluation of the effects of new drugs to be used in epilepsy treatment.